Biomaterials for mRNA delivery. (17th August 2015) - Islam, Mohammad Ariful; Reesor, Emma K. G.; Xu, Yingjie; Zope, Harshal R.; Zetter, Bruce R.; Shi, Jinjun
Abstract : Schematic representation of various biomaterial-based systems for mRNA delivery: (a) protamine–mRNA complex; (b) lipid nanoparticle; (c) lipid nanoparticle with inorganic compounds ( e.g. apatite); (d) cationic polymeric nanoparticle; (e) lipid–polymer hybrid nanoparticles including (i) mRNA–polymer complex core surrounded by a lipid shell and (ii) polymer core surrounded by a lipid shell with mRNA absorbed onto the surface; and (f) gold nanoparticle. Abstract : Messenger RNA (mRNA) has recently emerged with remarkable potential as an effective alternative to DNA-based therapies because of several unique advantages. mRNA does not require nuclear entry for transfection activity and has a negligible chance of integrating into the host genome which excludes the possibility of potentially detrimental genomic alternations. Chemical modification of mRNA has further enhanced its stability and decreased its activation of innate immune responses. Additionally, mRNA has been found to have rapid expression and predictable kinetics. Nevertheless, the ubiquitous application of mRNA remains challenging given its unfavorable attributes, such as large size, negative charge and susceptibility to enzymatic degradation. Further refinement of mRNA delivery modalities is therefore essential for its development as a therapeutic tool. This review provides an exclusive overview of current state-of-the-art biomaterials and nanotechnology platforms for mRNA delivery, and discusses future prospects to bring these exciting technologies into clinical practice.